Leiomyosarcoma of the esophagus - Filartiga Lacroix, Aníbal; Wattiez González, Carlos Raúl; Giménez Villarejo, Alejandro; Lemir Marchese, Pablo Ernesto (Cirugía del Uruguay, 1997)
Esophageal leíomyosarcoma is an ínfrequent non-epthelíal malígnante tumor very díffícult to díagnose preoperatívely. The diagnosis is based on baríum swallow, endoscopy and bíopsy. CT sean can be helpful for stagíng.